Investigation of temperature dependence of Raman and photoluminescence analysis of YBa2Cu3O7 (YBCO) doped with SiO2 nanoparticles - Almessiere Munirah A. (Science of Sintering, 2018)
We report the effect of SiO2 nanoparticles (12 nm) in YBa2Cu3O7 (YBCO) matrix. The samples YBCO and SiO2+YBCO are fabricated by a conventional solid-state reaction method, in ambiance conditions. We analyze these samples using X-ray diffraction (XRD), resonant Raman, environmental scanning electron microscopy (ESEM), and Photoluminescence (PL) as a function of temperature in the range from 77 to 837 K. The XRD confirm that the doped YBCO still displays a perovskite structure with the orthorhombic Pmmm phase. The Rietveld refinement confirms that SiO2 nanoparticles induce not only a strong effect on the oxygen’s O(5) and O(8) positions but also an elongation of the unit cell along the c-axis. The PL intensity of pure YBCO is more intense than the doped one that is mainly composed of two bands located at 2.4 eV and 1.88 eV. We simulate the PL intensity with temperature using the Bose-Einstein model with two activation energies corresponding to some specific vibration mode energies. The simulation reveals that the exchange energy between different levels in pure and doped YBCO is conducted by only two vibrations modes that are strongly linked to the oxygen and copper atoms in the YBCO matrix. We determine the evolution of Raman mode frequencies at 340 and 500 cm−1 with temperature using the Lorentzian function at q = 0 of the Balkanski model.